Cumulative damage of welded joints - Gurney, T. R. (Woodhead Pub. and Maney Pub. on behalf of the Institute of Materials, Minerals & Mining ; CRC Press, 2006)
Annotation Fatigue is a mechanism of failure that involves the formation of cracks under the action of different stresses. Stresses can be a wide range of magnitudes. To avoid fatigue it is essential to recognise at the design stage that the loading is such that fatigue may be a possibility and to design the structure with inherent fatigue strength. However fatigue strength is not a constant material property. It may be assessed by fracture mechanics, but such characteristics are based on quantitative analysis and mere assumption. Fatigue cracks are exceedingly difficult to see, particularly in the early stages of crack growth. Cracks can progress to a significant extent before they are even discovered. This book is primarily concerned with fatigue under variable amplitude loading, unlike most tests performed under constant loads. CONTENTS The constant amplitude database; Residual stresses; Variable amplitude loading and testing; Tests under two and three level loading; The influence of spectrum shape and block length; The influence of narrow and wide band loading; The influence of cycles of small stress range; Design for variable amplitude loading; More on the fracture mechanics approach - the effect of stress interaction.
Keywords: Welded joints -- Fatigue.; elektronické knihy; electronic books